A Newly Designed "SkyWalker" Robot Applied in Total Knee Arthroplasty: A Retrospective Cohort Study for Femoral Rotational Alignment Restoration. Issue 8 (27th June 2022) - He, Rui; Sun, Mao‐lin; Xiong, Ran; Yang, Peng‐fei; Lei, Kai; Liu, Li‐ming; Yang, Liu; Guo, Lin
Abstract : Objective: This study explored whether robotic arm‐assisted total knee arthroplasty (RATKA) has the advantage of restoring femoral rotational alignment compared to conventional total knee arthroplasty (COTKA). Methods: Sixty patients (45 women and 15 men) attending our department from May 2019 to December 2020 were selected and divided into two groups, with 30 patients in each group, according to whether they underwent COTKA or RATKA. Femoral rotational alignment results, such as, posterior condylar angle (PCA), patella transverse axis‐femoral transepicondylar axis angle (PFA), radiological findings, such as, hip‐knee‐ankle angle (HKA), lateral distal femoral angle (LDFA), and medial proximal tibial angle (MPTA), and operative data (operation time, intraoperative blood loss, tourniquet time, and length of stay (LOS), and clinical outcomes, such as maximum knee flexion angle (MKFA), Knee Society Score (KSS), and Western Ontario Mac Master University Index Score (WOMAC) were compared within and between the two groups. Results: PCA and PFA in the RATKA group were (0.6 ± 0.3)° and (0.9 ± 0.3)°, respectively, which were smaller than (1.5 ± 2.0)° and (3.1 ± 1.1)° in the COTKA group ( P  < 0.05), and were closer to 0°; the differences in HKA, LDFA, and MPTA were not statistically significant. With the exception of the LDFA, the HKA, MPTA, PCA, and PFA improved in both groups after surgery ( P  < 0.05). The blood loss and the LOS of RATKA group were 192.3 ± 23.1 mL and 8.2 ± 1.4 days, which were less than 203.7 ± 29.8 mL and 9.3 ± 1.1 days of the COTKA group, but the operation time showed no statistically significant difference, and the tourniquet time was longer ( P  < 0.05). The MKFA in the RATKA group was (123.0 ± 3.7)°, which was greater than (116.3 ± 4.6)° in the COTKA group ( P  < 0.05). In terms of scores, the postoperative results were better than the preoperative results in both groups ( P  < 0.05). However, there was no statistically significant difference between the groups. Conclusion: The accuracy of femoral rotational alignment reconstructed achieved by RATKA is significantly better than that of COTKA and is more conducive to the recovery of knee flexion function after surgery; although RATKA reduces intraoperative blood loss and postoperative LOS, the short‐term clinical efficacy comparison has not yet demonstrated the advantages of robotic technology, and a more optimized design is needed to improve the efficiency of RATKA surgery. Abstract : The short‐term clinical efficacy of RATKA was satisfactory, and it could achieve the same goals as COTKA to correct knee deformity, relieve pain and improve the patients' quality of life. RATKA is more minimally invasive and could restore more accurate femoral rotation alignment.